ENSURING THE FINANCIAL SUSTAINABILITY OF JOINT STOCK COMPANIES AND ITS SCIENTIFIC AND METHODOLOGICAL BASIS - Shernayev, Akbar (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
The main goal of the article is to develop a scientific proposal and practical recommendations regarding the importance of financial strategy in ensuring the financial stability and growth of joint-stock companies. It covers objectives such as setting in motion other mechanisms for joint-stock companies to operate in accordance with their status in accordance with market relations.